Controlled Growth of Single‐Crystal Twelve‐Pointed Graphene Grains on a Liquid Cu Surface. (10th July 2014) - Geng, Dechao; Meng, Lan; Chen, Bingyan; Gao, Enlai; Yan, Wei; Yan, Hui; Luo, Birong; Xu, Jie; Wang, Huaping; Mao, Zupan; Xu, Zhiping; He, Lin; et al.
<x xml:space="preserve">Abstract</x> The controlled fabrication of single‐crystal twelve‐pointed graphene grains is demonstrated for the first time by ambient pressure chemical vapor deposition on a liquid Cu surface. An edge‐diffusion limited mechanism is proposed. The highly controllable growth of twelve‐pointed graphene grains presents an intriguing case for the fundamental study of graphene growth and should exhibit wide applications in graphene‐based electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>